Gene Expression Dynamics in Major Endocrine Regulatory Pathways along the Transition from Solitary to Social Life in a Bumblebee, Bombus terrestris - Jedlička, Pavel; Ernst, Ulrich R.; Votavová, Alena; Hanus, Robert; Valterová, Irena (Frontiers in Physiology, 2016)
Understanding the social evolution leading to insect eusociality requires, among other, a detailed insight into endocrine regulatory mechanisms that have been co-opted from solitary ancestors to play new roles in the complex life histories of eusocial species. Bumblebees represent well-suited models of a relatively primitive social organization standing on the mid-way to highly advanced eusociality and their queens undergo both, a solitary and a social phase, separated by winter diapause. In the present paper, we characterize the gene expression levels of major endocrine regulatory pathways across tissues, sexes, and life-stages of the buff-tailed bumblebee, Bombus terrestris, with special emphasis on critical stages of the queen’s transition from solitary to social life. We focused on fundamental genes of three pathways: (1) Forkhead box protein O and insulin/insulin-like signaling, (2) Juvenile hormone signaling, and (3) Adipokinetic hormone signaling. Virgin queens were distinguished by higher expression of forkhead box protein O and downregulated insulin-like peptides and juvenile hormone (JH) signaling, indicated by low expression of methyl farnesoate epoxidase (MFE) and transcription factor Krüppel homolog 1 (Kr-h1). Diapausing queens showed the expected downregulation of JH signaling in terms of low MFE and vitellogenin (Vg) expressions, but an unexpectedly high expression of Kr-h1. By contrast, reproducing queens revealed an upregulation of MFE and Vg together with insulin signaling. Surprisingly, the insulin growth factor 1 (IGF-1) turned out to be a queen-specific hormone. Workers exhibited an expression pattern of MFE and Vg similar to that of reproducing queens. Males were characterized by high Kr-h1 expression and low Vg level. The tissue comparison unveiled an unexpected resemblance between the fat body and hypopharyngeal glands across all investigated genes, sexes, and life stages.